GROWTH VOLATILITY AND GOVERNMENT EXPENDITURE IN LOW AND MIDDLE INCOME COUNTRIES: A DYNAMIC PANEL ANALYSIS - Turan, Taner; Iyidogan, Pelin Varol (Babes-Bolyai Univ, 2017)
We examine the relation between the government consumption expenditure and output growth volatility in 57 low and middle income countries by using both static and dynamic panel methods. It seems that the results of these methods largely differ from each other. Contrary to some previous results reported in the literature, we present a strong evidence for a negative relation between government expenditure and volatility in low and middle income countries. We also conclude that the volatilities of government consumption, trade openness and investment are significant in explaining the growth volatility. To have a more stable economy, policy makers in these countries should pay more attention to some issues. In this context, we think that a change in the tax and expenditure system in order to make automatic stabilizers work better would be helpful. Additionally, it is important to have a sound fiscal and monetary position to effectively carry out countercyclical policies when needed. Moreover, adopting and implementing clear and flexible rule-based economic policies should be considered. Finally, improving the institutional structure and policy making capacity must be an ultimate aim to reduce the economic volatility.
Keywords: growth volatility; government expenditures; low and middle income countries; dynamic panel methods